Ways of formation(training) of water-fuel mixes both accumulation settling-vat water and their property in fuel tanks aircraft - Туз, М. Д.; Кер’якос, Д. (Proceedings of National Aviation University (archive), 2000)
Investigated are the conditions and mechanisms of accumulation of free water in aircraft torsion-box fuel systems. Determined is a quantitative balance between phases and conditions in the torsion-box fuel tanks at every stage of operation